2010
DOI: 10.1111/j.1349-7006.2010.01575.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating vitamin D and colorectal adenomas in Japanese men

Abstract: Accumulating evidence suggests that vitamin D has anticarcinogenic effects. However, it is unclear whether the nutrient is involved in the early stage of colorectal carcinogenesis. We examined the association between circulating vitamin D concentrations and colorectal adenomas in Japanese men. The study subjects comprised 656 cases of colorectal adenomas and 648 controls with normal colonoscopy among male self defense officials receiving a pre-retirement health examination between 1997 and 2004. Plasma or seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 34 publications
0
34
0
1
Order By: Relevance
“…Thus, the colon can produce 1,25(OH) 2 D from 25(OH)D locally to control the genes that inhibit and suppress carcinogenesis. If a cell becomes malignant, then 1,25(OH) 2 D can induce apoptosis and inhibit angiogenesis, thereby reducing the potential for the malignant cell to survive [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the colon can produce 1,25(OH) 2 D from 25(OH)D locally to control the genes that inhibit and suppress carcinogenesis. If a cell becomes malignant, then 1,25(OH) 2 D can induce apoptosis and inhibit angiogenesis, thereby reducing the potential for the malignant cell to survive [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although 90-95% of all vitamin D is produced in the skin by the action of sunlight [6][7][8], most observational studies were limited to assessing only poorly measured dietary vitamin D intake and the findings from these studies have mostly been null [9][10][11][12][13][14][15][16][17][18][19][20][21]. Most of the studies that measured the circulating vitamin D concentration have had also some limitations of the enrolled study population, such as the enrolled participants were evaluated for the status of only the distal colorectum using sigmoidoscopy [12,13,22,23], they were taking chemopreventive agents or placebo for a chemoprevention trial [20,24], they had symptoms that needed colonoscopic evaluations [4,25] or they were all of one gender [22,26]. Therefore, even though the studies showed a trend that a better vitamin D status lowered the risk of colorectal adenoma, the findings from these studies have remained inconsistent [12,13,20,[22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each category of UV exposure history, we combined the exposure across each of the three decades of life recorded for all participating women (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) [30][31][32][33][34][35][36][37][38][39] years) the first categories represent exposure accumulating over successive decades from age 10 to 39 years, whereas the last category reflects exposure in adult age only (i.e., 20-39 years). Solarium use is separated into four categories representing cumulative exposure from age 10 to 39 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, the IARC report has been criticized as being biased against the hypothesis of a beneficial effect of vitamin D on cancer incidence (5). Although ecological studies have suggested that there is a beneficial effect of sun exposure on the risk of some cancers, such as ovarian, bladder, brain, and lung (6)(7)(8), and seasonal variations in breast and colorectal cancer incidence rates suggest that serum 25(OH)D levels may be inversely associated with risk (9,10), almost no prospective studies have yet evaluated these associations. Furthermore, whether host pigmentary characteristics are relevant to the risk of developing other cancers, or whether they modify the effects of UV exposure, remains unclear.…”
Section: Introductionmentioning
confidence: 99%